1970
DOI: 10.1079/bjn19700019
|View full text |Cite
|
Sign up to set email alerts
|

Volatile fatty acid production in the rumen of cattle given an all-concentrate diet

Abstract: I . Short-term in vitro incubations of whole rumen contents have-been used to measure the rate of production of volatile fatty acids (VFA) in two heifers given a diet containing 85 yo barley and 15 yo protein-mineral-vitamin supplement. Daily intake of the diet was restricted to 5.1 kg which was given in three equal feeds. In one heifer (no. 794), VFA production was measured over a 24 h feeding cycle; in the other (no. 832), a single 6 h feeding period was examined.2. The feeding schedule outlined above was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 23 publications
1
20
1
1
Order By: Relevance
“…The pH values tend to peak in the moments before feed intake, begin to fall afterward, and reach the minimum between 3 and 6 h after feed intake depending on the ration (Duffield et al, 2004;Marden et al, 2005;Palmonari et al, 2010). As acid production decreases, volatile fatty acid absorption and rumen buffer capacity (mainly from saliva) increase, and pH begins to recover initial values; this process is estimated to last approximately 18 h (Whitelaw et al, 1970;Maekawa et al, 2002;Palmonari et al, 2010). The pH pattern observed in TMR animals suggests that most of the feed is consumed as soon as it is delivered.…”
Section: Daily Ph Variationsmentioning
confidence: 99%
“…The pH values tend to peak in the moments before feed intake, begin to fall afterward, and reach the minimum between 3 and 6 h after feed intake depending on the ration (Duffield et al, 2004;Marden et al, 2005;Palmonari et al, 2010). As acid production decreases, volatile fatty acid absorption and rumen buffer capacity (mainly from saliva) increase, and pH begins to recover initial values; this process is estimated to last approximately 18 h (Whitelaw et al, 1970;Maekawa et al, 2002;Palmonari et al, 2010). The pH pattern observed in TMR animals suggests that most of the feed is consumed as soon as it is delivered.…”
Section: Daily Ph Variationsmentioning
confidence: 99%
“…Si l'on admet que la lignine est pratiquement indigestible (Journet et Jarrige, 1962) (Hungate, 1943 ;Sugden, 1953 ; Kanegasaki, 1969 ;Bonhomme et Durand, 1974 ;Jouany et al, 1977 ;Grolière et al, 1980 ;Sènaud et al, 1980) cide avec plusieurs observations déjà faites dans notre laboratoire (Collombier, 1981) ou à l'étranger (Whitelaw et al, 1970 Gill, 1971 ;Itabashi et Kandatsu, 1975) s'explique à la fois par une dégradation des protéines alimentaires (Warner, 1955 ;Williams et al, 1961) et bactériennes (Gutierrez et Hungate, 1957 ;Gutierrez, 1958 ;Coleman, 1975) ingé-rées par les ciliés.…”
unclassified
“…HUNGATE15) suggested that rumen can be regarded as a complete continuous fermentation system in the case where the volume of rumen, the rate of salivary secretion and the rate of passage of digesta through the rumen are stable all day long and that if an animal has been fed by subdividing the daily ration into portions which were fed at regular and frequent intervals over a day, its rumen would resemble the continuous fermentation model FAICHNEY6) reported that the range from minimum to maximum values observed during a day for the rumen VFA concentration of the sheep fed lucern pellet decreased from 4 .5-16.5mmol/ dl to 8.0-11.0mmol/dl corresponding to an increase in the frequency of feeding from once to eight times daily. WHITELAW et al 8) similarly described that increasing the frequency of feeding of a barley diet to heifers from once to three times daily decreased the range of rumen VFA in a day from 6.5-15.5mmol/dl to 6.0-11.0mmol/dl. The present study showed that the ranges of the rumen VFA in the sheep fed the hay or concentrate diet in free access were the same as those observed when increasing the frequency of feeding.…”
Section: Discussionmentioning
confidence: 98%